Gender Perceptions: Employer Branding Through Attractiveness, Job Characteristics and Organizational Attributes - Aslam, Summer; Mason, Cordelia; Zakria, Asma; Farid, Mohd (American Journal of Trade and Policy, 2016)
The novelty of employer branding is undeniable in HR practices. However, the pair studies are also found in employer branding with the perception of gender. A gender difference is said to occur when male and female react differently in perceptions. In Pakistan, human capital is an inadequacy in bank jobs and female less appearance in the sector creates more shortage of skilled employees. However, the results reported have given an insignificant difference between male and female in the perception of employer branding. Moreover, the gender disparity has no borders, so re-justification is an admirable in another region. Hence, a significant relationship exists between employer branding and intention to apply. Intention to apply is a central dealing with recruitment as appears with the wish for of submitting a job application. Furthermore, the wider applicant pool can achieve with employer branding. Employers can persuade to potential employees through attractiveness, unique organizational attributes and job characteristics. Concluded, banks in Pakistan can increase a wider applicant pool with the implementation of employer branding. Data Analysis was done by using SPSS and smart PLS. Future recommendations and implications are at the end.